Pharmacokinetics of a Standardized Extract of Centella asiatica ECa 233 in Rats - Anukunwithaya, Tosapol; Tantisira, Mayuree H.; Tantisira, Boonyong; Khemawoot, Phisit (Planta Medica, 2017)
ECa 233, a standardized extract of Centella asiatica, has been found to exhibit various positive neurological effects and to have a good safety profile. The present study aimed to explore the disposition kinetics of ECa 233, containing madecassoside (53.1 %) and asiaticoside (32.3 %), in rats. The extract was intravenously or orally administered at doses from 50 to 200 mg/kg. Plasma, tissues, urine, and feces were collected at time points from 0 to 48 h after dosing. The levels of madecassoside and asiaticoside, as well as their postulated triterpenic metabolites, madecassic acid and asiatic acid, in biological samples, were simultaneously measured by liquid chromatography-tandem mass spectrometry. The results showed that all animals had a good tolerability for ECa 233, whereas madecassic and asiatic acids were found in negligible amounts after pharmacokinetic assessment. Madecassoside and asiaticoside demonstrated rather similar absorption and tissue distribution profiles. They were rapidly absorbed, reaching maximum levels within 5–15 min after oral administration, but they had poor oral bioavailability, less than 1 %. Both triterpenoids were extensively distributed in the brain, stomach, and skin within 1 h and remained there for at least 4 h after dosing. Madecassoside and asiaticoside in ECa 233 were mainly excreted as an unchanged form after being injected, and exclusively as triterpenic acid metabolites in feces after oral administration. The pharmacokinetic results obtained could provide some guidance for an appropriate dosing regimen of ECa 233 in future studies. This study also provided the first evidence demonstrating the presence of madecassoside and asiaticoside in their target tissues.
Keywords: Centella asiatica; Apiaceae; ECa 233; madecassoside; asiaticoside; pharmacokinetics